Association between neutropenia and response to ramucirumab and paclitaxel in patients with metastatic gastric cancer. Issue 6 (July 2020) - Roviello, Giandomenico; Conca, Raffaele; D'Angelo, Alberto; Multari, Andrea Giovanni; Paganini, Giovanni; Chiriacò, Giorgio; Petrioli, Roberto; Corona, Silvia Paola; Rosellini, Pietro; Aieta, Michele
Abstract : The aim of this study was to evaluate if the occurrence of neutropenia is correlated with response to ramucirumab plus paclitaxel for metastatic gastric cancer. This is a retrospective study of patients treated with ramucirumab plus paclitaxel. Fifty-three patients were evaluated. Among these, 10 patients (26.5%) developed grade ≥3 neutropenia. Patients with grade ≥3 neutropenia reported a progression-free survival of 6.6 months (95% confidence interval 3.3–8.4) and overall survival of 11 months (95% confidence interval 5.9–13.1) vs. 4.4 months (95% confidence interval 3.9–5.2) and 8.7 months (95% confidence interval 7.8–10.1) respectively in patients' group with lower grade events. Our analysis seems to suggest that the occurrence of neutropenia predicts response to treatment with ramucirumab and paclitaxel.